P24 An audit reviewing the provision of HIV pre-exposure prophylaxis. (16th June 2022) - Cartner, Emma; Ismail, Muhammad; Loftus, Hannah
Abstract : Introduction: HIV Pre-exposure prophylaxis (PrEP) is a prevention strategy which uses antiretroviral drugs to prevent acquisition of HIV in high-risk individuals. This audit was an evaluation of a local PrEP service and aimed to assess and improve the provision of PrEP. Methods: A retrospective case notes analysis was performed on a random sample of patients who commenced PrEP between October 2020 and June 2021. Twenty-seven audit standards were derived from BHIVA/BASHH guidelines on the use of HIV PrEP (2018), with a target of 100% for all standards. Data was collected using a standardised proforma and analysed using Microsoft Excel. Results: The sample comprised fifty-one patients: All were cisgender males, with a mean age of 31.8 years old (range 19-62). Three (6%) patients were seen face-to-face, 48 (94%) had telephone consultations. Table 1 shows service performance across 10 pertinent outcomes. Discussion: There was high adherence to standards regarding appropriate prescription of PrEP; baseline investigations before prescribing PrEP; and counselling on risks and benefits of PrEP. Areas for improvement include the prescription and dispensing of PrEP in a timely manner; ensuring prompt review of investigations results; and accurate documentation of co-morbidities, medications, and their interactions with PrEP. Demographic data collected highlighted the limited population accessing this service. Proposed interventions include: Staff education around co-morbidities and medications which can impact PrEP prescription Increase awareness of PrEP in populations other than MSM Electronic reminders to review results within a set period Re-audit in a year's time to assess the impact of interventions